Female reproductive system of ant species of the subfamily ponerinae: Review and new data - CamargoMathias, M. I.; Thiele, E.; Caetano, F. H. (California State University, 1997)
Literature data about the female reproductive system of some species in the subfamily Ponerinae are presented. Our project objective to compile a report containing the largest possible number of data about the reproductive system in Ponerinae for a better understanding of the reproductive biology of these Insects, was completed.
Keywords: Ponerinae; ants; ovaries morphology; review